Análise química de nutrientes em alimentos de transição preparados no domicílio para o almoço de lactentes de dois estratos socioeconômicos de Belém, Pará - Portella, Márcia Bitar [UNIFESP] (2009)
Objectives: The objectives of this study involving infants of two social strata in Belém, Pará were determined by chemical analysis, the nutritional composition of macronutrients, energy, sodium and iron from food prepared at home for lunch these children, and evaluate based on the information food intake, the quantitative role of transitional food as a source of energy, protein, fat, iron and sodium in relation to nutritional recommendations in the two social strata. Methods: We carried out a transversal study with 78 children aged 6 to 18 months divided into two social strata who receive transitional food prepared at home. Samples were collected food for lunch for chemical analysis. All children had their nutritional status assessed and estimated daily food intake was based on the 24 hour diet recall method. Results: The results of chemical analysis of food samples revealed iron deficiency and excess sodium in both social strata, the higher sodium content in food samples of infants in the lowest stratum. The 24 hour diet recall method showed that most infants of the two social strata consumed over 120% of energy for the estimated energy requeriments (EER) and above 120% carbohydrates of adequate intake (AI). All infants consumed more than the amount of protein and 50% recommended dietary allowances (RDA) ingest iron below the recommended dietary allowances (RDA). Regarding sodium, consumption was up 120% of the AI, the daily intake of meals of low socioeconomic strata had higher levels of sodium in the higher socioeconomic strata. The energy content from protein was found above the recommended values, the average contribution of fat is below the recommended and energy from carbohydrates was within the expected range. The Z scores of weight-age and height-age were higher in the group of high socioeconomic stratum. It was lack of height-age at 10.8% (4/37) in children of low socioeconomic stratum and 2.4% (1/41) in children of higher socioeconomic stratum. The percentage of overweight were similar in both groups, both for the weight-height. Conclusion: According to the two instruments, chemical analysis and food survey, it was appropriate as to energy, proteins, lipids and carbohydrates in both social strata. It was shown, also, excessive sodium and iron deficiency.